Determination of Liver Cirrhosis by Liver Function Tests, Lipid Peroxidation (MDA) and Antioxidant Enzyme (SOD) - Dr. Asha Gupta; Dr. Dipika Shyoran; Dr. Pankaj Kumar Meena, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Liver cirrhosis is a severe condition characterized by the replacement of healthy liver tissue with scar tissue, impairing its function. Caused by various liver diseases, it is a global health issue causing 1.47 million deaths in 2019. Common causes include chronic alcohol abuse, viral infections, obesity, diabetes, high cholesterol, hemochromatosis, Wilson's disease, autoimmune hepatitis, primary biliary cholangitis, and primary sclerosing cholangitis. Prevention and management include lifestyle changes, medications, and liver transplants. Aims & Objectives: The study aims to determine Liver Cirrhosis by analyzing markers of LFT, MDA, and SOD, estimating SGOT/SGPT ratio, albumin/globulin ratio, MDA, and SOD, and examining their relationship. Materials and Methods: This study involved 100 patients, 50 with Liver Cirrhosis and 50 normal. Samples were collected from the Department of Medicine and tested at the Department of Biochemistry. The tests included serum SGPT by Kinetic UV Method, SGOT by Kinetic UV Method, Total protein by Roche Cobas 6000 method, Albumin by BCG Method, Globulin by Calculated manually, MDA by Jeans CD method, and SOD by Marlund and Marlund Method. Results: Liver cirrhosis patients have higher SGOT/SGPT ratio (2.56±0.38 U/L) and Albumin/Globulin ratio (0.81±0.06 g/dl) decreased compared to normal individuals. Serum Malondialdehyde (MDA) and Superoxide Dismutase (SOD) levels also differ between Liver Cirrhosis patients and normal individuals. Serum MDA (0.37±0.02 nmol/ml) increases in Liver Cirrhosis patients, while SOD (4.41±1.43 units/ml) decreases in Normal individuals. These findings highlight the importance of monitoring liver cirrhosis patients. Discussion: The study found that Liver Cirrhosis patients have a higher SGOT:SGPT ratio, Albumin: Globumin ratio, Malondialdehyde (MDA), and Serum Superoxide Dismutase (SOD) values compared to normal individuals. These results are consistent with previous studies, and further research is needed to estimate the relationship between SOD and Liver Cirrhosis. The results align with previous research and suggest further research is needed to better understand the relationship between these factors. Summary & Conclusion: The study, involving 50 individuals with Liver Cirrhosis and normal group, found that SGOT and SGPT ratios increased in Liver Cirrhosis patients, while Albumin and Globulin ratios increased. Malondialdehyde (MDA) also increased in Liver Cirrhosis patients, and Superoxide Dismutase (SOD) decreased in Liver Cirrhosis patients, but further research is needed.The conclusion was SGOT:SGPT ratio, Albumin: Globulin ratio, and Serum MDA are key markers for liver disorders detection, but further research is needed to understand Serum SOD levels.